Hydrophobic polyurethane foams reinforced with microcrystalline cellulose for oil spill clean up - Matheus Vinícius Gregory Zimmermann; Eduardo Junca; Marina Kauling de Almeida; Lara Vasconcellos Ponsoni; Ademir José Zattera; Tiago Mari; Ruth Marlene Campomanes Santana (Polímeros, 2024)
Abstract Oil spills into water have been an environmental concern since the beginning of large-scale oil extraction. In this study, flexible open-cell polyurethane (PU) foams with added microcrystalline cellulose (MCC) were formulated and chemically modified with organosilane for use as an absorbent system for oil spill cleanup in water. The influence of cellulose concentration on mechanical properties and chemical treatment with organosilane was evaluated. The primary findings indicate that the surface treatment of the solid fraction of the foams was effective, as indicated by the contact angle, increasing the hydrophobicity of the samples. Because of the increased roughness of the PU solid fraction and the cellulose reactivity, the mechanical compressive strength and thickness of the organosilane layer increased with increasing MCC content. However, the higher the MCC content in the composition, the higher was the density, which reduced the sorption capacity of the samples.